Investigating the Impact of Leadership Style on Workforce Productivity in Information Technology Captive Centers in India - Padmanabha, Venugopal (Digital Repository of Theses - SSBM Geneva, 2025)
This thesis explores the significant impact of leadership styles on workforce productivity in IT Captive Centers in India. Leadership styles can foster a positive work environment or create obstacles that hinder productivity and job satisfaction. Key issues include inadequate direction and communication, Autocratic decision-making, and limited trust and transparency. Our comprehensive analysis identifies and categorizes commonly observed leadership styles (Democratic, Autocratic, and Laissez-faire) and scrutinizes their impacts on employee motivation, engagement, and job satisfaction. We employ a combination of surveys, interviews, and performance metric analysis techniques to develop a holistic understanding of the relationship between leadership styles and workforce productivity. The study underscores the importance of an in-depth investigation into the influence of leadership style on workforce productivity for a deeper understanding of IT Captive Centers in India. By examining organizational dynamics and identifying strategies to maximize productivity, companies can enhance their ability to motivate and engage employees successfully. The insights gained will assist organizations in making well-informed decisions when selecting and developing leaders. The leadership style practiced within these Captive Centers plays a pivotal role in shaping employee performance and determining overall organizational success